Project-Based Learning Management on Geometrical Optics for Encouraging Problem Solving Ability and Scientific Attitudes of 11th Grade Students: - - Longjamnong, Natwipha; Worakham, Paisarn (Ratchaphruek Journal, 2021)
This research was the study of problem-based learning management for enhancing problem solving ability and scientific attitude. The purposes were: 1) To develop the project-based learning management with the efficiency criteria (E1/E2) of 80/80; 2) To compare the students’ problem-solving ability before and after learning; and 3) To study the students’ scientific attitudes after learning. The sample from cluster random sampling consisted of 42 students studying in Matthayomsuksa 5/10, in the 1st semester of academic year 2020, at Sarakhampitthayakhom School, Muang District, Maha Sarakhom Province,. The research instruments were project-based learning management plans, the students’ problem-solving subjective test, and the scientific attitudes test. Data were analyzed by mean, standard deviation, percentage, and dependent sample t-test. The research outcomes were: 1) The project-based learning management concerning Geometrical Optics had efficiency of 88.51/82.25; 2) After learning, students had problem solving ability significantly higher than those before at .01 level, and also had the scientific attitudes at the high level.